Regulating intra-annual agricultural water use under climate and price uncertainty - Reynaud A. (Economics of drought and drought preparedness in a climate change context, 2010)
We propose a framework allowing to optimize land allocation across crops and intra-annual water use for a farmer facing both climate and price uncertainty. Agricultural production technologies are represented through climate-contingent crop yield functions estimated using data generated by a biophysical crop growth model. These crop yield functions are then integrated into a decision model under uncertainty. An empirical application is developed for a region located in Southwest of France. We analyze in particular how the timing of climatic uncertainty modifies farmer's optimal decisions.
2. International Conference on Drought Management, 2010/03/04-06, Istanbul (Turkey)